Efficacy and safety of sintilimab plus doxorubicin in advanced soft tissue sarcoma: A single-arm, phase II trial - Tian, Zhichao; Dong, Shuping; Zuo, Wenli; Li, Po; Zhang, Fan; Gao, Shilei; Yang, Yonghao; Li, Chao; Zhang, Peng; Wang, Xin; Wang, Jiaqiang; Yao, Weitao (Frontiers in Pharmacology, 2022)
Background: Chemoimmunotherapy is safe and efficacious in treating many types of malignant tumors. However, clinical data demonstrating the effect of this combination treatment in patients with metastatic soft tissue sarcoma (STS) are currently limited. This study evaluated the safety and efficacy of a programmed cell death protein 1 (PD-1) inhibitor plus doxorubicin in patients with advanced STS who failed previous systemic therapy. Methods: This was a single-center, single-arm, open-label phase II trial. Patients with unresectable or metastatic STS who had previously failed systemic therapy were enrolled. Patients received up to six cycles of doxorubicin and sintilimab (a PD-1 inhibitor), while sintilimab treatment continued for up to 2 years. Primary outcomes were objective response rate (ORR) and safety. Univariate Cox proportional hazards model was used to analyze the relationship between clinicopathological parameters and progression-free survival (PFS). Results: A total of 38 patients (20 men and 18 women) were enrolled in this study. The overall ORR was 39.5%, disease control rate was 71.1%, and the median PFS was 4.5 months {95% confidence interval (CI), 3.0–8.5 months}. The adverse events (AEs) associated with the combined treatment were mild, manageable, and well-tolerated. The most common grade 3 or higher AEs were hematologic, including leukopenia (21.1%), anemia (18.4%), and thrombocytopenia (18.4%). Patients with undifferentiated pleomorphic sarcoma (UPS) or dedifferentiated liposarcoma had a significantly longer PFS than those with other pathological subtypes {hazard ratio (HR) = 0.42, 95% CI 0.21–0.83; P = 0.013}. There was no significant difference in the median PFS between patients who had previously received anthracycline-based chemotherapy and those who had not (HR = 0.74, 95% CI 0.34–1.58, P = 0.43). Conclusion: Sintilimab plus doxorubicin is a safe and promising treatment for patients with advanced STS who have failed previous systemic therapy (including anthracycline-based chemotherapy). The efficacy of this combination therapy in UPS and dedifferentiated liposarcoma is superior to that in other sarcomas.